Financing of Secondary Education in Ukraine: Statistical Assessment - PashkovskaА. Yu. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
As reforms of the secondary education system in Ukraine require comprehensive statistical analysis of its financing at national and regional level, the article aims to study statistical data on financing of general secondary education in Ukraine. To compare the trend in education financing in Ukraine and other countries, correlations between the economic performance and the share of population with tertiary education in selected countries (in 2014), and government spending on education in EU countries (in 2014) are used. Ukrainian tendencies in the education financing are studied by domestic official data on education spending by education level (2007–2014), the structure of government spending on secondary education by spending purpose (2007–2014), education spending by education level (2007–2014). Also, data from the survey of Ukrainian households are taken to analyze households’ spending on education, which shows that now the Ukrainian population can not afford to invest in education. Regional aspect of the education financing is analyzed by use of data on average spending per pupil by Ukrainian region. Yet, the analysis has to be limited due to missing data on private sources of secondary education financing and use of private funds by territory, type of education establishment and education level. Special sample survey of pupils’ parents as part of the monitoring of secondary education is proposed, to collect data about private (household) spending on secondary education in Ukraine. The conclusion is made that the secondary education in Ukraine gets too little money from the government given the economic crisis and limited resources, which is in outward contrast with developed countries.